2019
DOI: 10.14716/ijtech.v10i1.2012
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Structural Study of Vertically Aligned Zinc Oxide Nanorods Grown on Spin Coated Seed Layers

Abstract: In this study, vertically aligned zinc oxide (ZnO) nanorod (NR) arrays were grown with the 2step method. Spin coating was used to apply the seed layer, and by increasing the number of repetitions (n), higher thickness of the seed layer was achieved. The effects of different seed layer thicknesses, spin coated at different rotational speeds (v) and how the variables (v and n) influence the morphological and crystal properties of the resulting ZnO NRs were analyzed. The effects of 1, 3, and 5 (n), with (v) of 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In this study, a CBD method was reported, involving the application of a waterbath machine as a heat source for the beaker container in order to grow ZnO NRs. is method was also used in the previous research to grow 1.0-1.5 μm long ZnO NRs [35]. e same method was used to grow ZnO NRs with a length of less than or equal to 1.0 μm.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, a CBD method was reported, involving the application of a waterbath machine as a heat source for the beaker container in order to grow ZnO NRs. is method was also used in the previous research to grow 1.0-1.5 μm long ZnO NRs [35]. e same method was used to grow ZnO NRs with a length of less than or equal to 1.0 μm.…”
Section: Introductionmentioning
confidence: 99%
“…An equal molar of HMTA was added and stirred at 70 °C for 2 h. Afterward, the seed solution was aged for 24 h at room temperature. [ 48 ] The aged ZnO seed solution was spun coated on cleaned FTO glass at 3000 rpm for 25 s. The substrate was annealed at 350 °C for 1 h.…”
Section: Methodsmentioning
confidence: 99%
“…An equal molar of HMTA was added and stirred at 70 °C for 2 h. Afterward, the seed solution was aged for 24 h at room temperature. [48] The aged ZnO seed solution was spun coated on cleaned FTO glass at 3000 rpm for 25 s. The substrate was annealed at 350 °C for 1 h. ZnO Nanosheets (ZnO NSs): Zinc acetate dihydrate Zn(CH 3 CO 2 ) 2 .2H 2 O (0.8 g) and 1.25 g of urea were dissolved in 50 mL of DI water and stirred for 30 min to obtain a homogeneous solution. After 30 min of stirring, NH 3 was added to adjust the pH until it reached 8.…”
Section: Methodsmentioning
confidence: 99%
“…The broad diffraction peaks indicate that the crystallite sizes of the ZnS NPs are small. The average crystallite sizes (L) were then estimated using the Scherrer equation (Yustanti et al, 2016;Bramantyo et al, 2019).…”
Section: Xrd Analysismentioning
confidence: 99%